Managing propagule pressure to prevent invasive species establishments: propagule size, number, and risk–release curve. Issue 4 (7th April 2021) - Stringham, Oliver C.; Lockwood, Julie L.
Abstract: There is considerable evidence that keeping propagule pressure low can drastically reduce establishment probability of potential invasive species. Yet, most management plans and research efforts fail to explicitly acknowledge all three of the components of propagule pressure: size, number, and the risk–release relationship. It is unclear how failing to specify one or more of these components can influence the efficacy of management plans in preventing invasive species establishment. Furthermore, even if all components are acknowledged and quantified, there currently is no mathematical tool available to calculate the levels of propagule pressure that ensure attainment of a predetermined, and system‐specific, target establishment probability. Here, we quantify the resulting uncertainty in establishment probability when one or more components of propagule pressure is unknown by using parameter uncertainty analysis on realistic values of propagule pressure. In addition, to aid in the development of management plans that explicitly set propagule pressure limits, we develop a propagule‐pressure sensitivity analysis that we use to determine the required reduction in levels for propagule size and number (representative of management actions) to maintain a target establishment probability. We show that the precision of establishment estimates is highly dependent on knowledge of all three propagule pressure components, where the possible range of values for establishment probability can vary by over 50% without full specification. In addition, our sensitivity analysis showed that propagule size and number can be altered independently or in conjunction to lower establishment probability below a target level. Importantly, our sensitivity analysis was able to specifically quantify how much reduction in a propagule pressure component(s) is needed to reach a given target establishment probability. Our findings suggest that quantifying the three components of propagule pressure should be a priority for invasive species prevention moving forward. Furthermore, our sensitivity analysis tool can serve to guide the development of new invasive species management plans in a transparent and quantitative manner. Together with information on the costs associated with approaches to reducing propagule pressure, our tool can be used to identify the most cost‐effective approach to prevent invasive species establishments.